This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Solution 1:
( 2 1 ) x = 4
( 2 1 ) x = ( 2 1 ) − 2
x = − 2 answer
Solution 2.
( 2 1 ) x = 4
taking the natural logarithm of both sides, we have
ln ( 2 1 ) x = ln 4
x ln 2 1 = ln 4
x = ln 0 . 5 ln 4
x = − 2 answer
Marvin, please use \ln for natural log operator. Operators must not be in italics.
( 2 1 ) x = 4
2 − x = 2 2
− x = 2 ⟹ x = − 2
x = lo g 2 1 ( 4 ) = − 2
Problem Loading...
Note Loading...
Set Loading...